2008
DOI: 10.1515/jbcpp.2008.19.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Piper betle on hepatic marker enzymes and tissue antioxidant status in D-galactosamine-induced hepatotoxic rats

Abstract: D-galactosamine is a well-established hepatotoxicant that induces a diffuse type of liver injury closely resembling human viral hepatitis. D-galactosamine by its property of generating free radicals causes severe damage to the membrane and affects almost all organs of the human body. The leaves of Piper betle L., a commonly used masticatory in Asian countries, possess several biological properties. Our aim is to investigate the in vivo antioxidant potential of P. betle leaf-extract against oxidative stress ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In the literature, several antioxidants have been investigated for their effects in preventing furan-induced toxicity in different organs and tissues (19, 21, 36, 41, 42). Augmented antioxidant capacity is critical in providing a hepatoprotective effect and counteracts the untoward effects of oxidative stress (35). Our literature review revealed no studies investigating the antioxidant effects of propolis treatment in the furan-induced hepatotoxicity model in rats.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, several antioxidants have been investigated for their effects in preventing furan-induced toxicity in different organs and tissues (19, 21, 36, 41, 42). Augmented antioxidant capacity is critical in providing a hepatoprotective effect and counteracts the untoward effects of oxidative stress (35). Our literature review revealed no studies investigating the antioxidant effects of propolis treatment in the furan-induced hepatotoxicity model in rats.…”
Section: Discussionmentioning
confidence: 99%
“…PB was reported to possess hepatoprotective action. Studies examined the effect of PB on various toxic compounds including cadmium, carbon-tetrachloride, D-galactosamine, and ethanol which showed PB extract significantly reduced liver injury caused by the toxic compounds [13][14][15][16]. PB extract exhibited high antioxidant activities [21].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous scientific studies reported therapeutic properties of PB [11,12]. PB was reported to exhibit hepatoprotective effect against various toxic insults including cadmium, carbon tetrachloride, ethanol, and D-galactosamine [13][14][15][16]. Hence, in the present study, we aimed to observe the effect of PB in hepatotoxicity caused by MS.…”
Section: Introductionmentioning
confidence: 98%
“…The extract at a dose of 200 mg/kg bw improved antioxidant levels such as lipid hydroperoxidase (LOOH), SOD, GSH, GSH peroxidise, vitamin E and vitamin C,decreased TBARS, hydroperoxidase and liver marker enzymes such as ALT, AST, alkaline phosphate (ALP) and gamma glutamyl transpeptidase (GGTP). 139 To evaluate the hepatoprotective activity of P . betle , Young et al induced liver fibrosis with carbon tetrachloride (CCl 4 ) and corn oil in Wistar rats.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%